FALLOPIAN TUBE CYST: A RARE COMPLICATION OF TUBAL STERILIZATION - Zahiruddin, Sana; Khan, Momna; Iftikhar, Maria (Journal of Ayub Medical College Abbottabad, 2016)
Tubal sterilization is one of the most commonly employed permanent method of contraception, although it is considered very safe, rarely a cyst may develop in the fallopian tube after sterilization which may undergo torsion resulting in patient presenting with acute abdomen. We are presenting a case of a middle aged women presenting to emergency room with severe lower abdominal pain, she had past history of tubal ligation done 12 years back. Pelvic ultrasound showed right sided ovarian cyst, emergency laparotomy was performed for suspected torsion of ovarian cyst, which revealed normal ovary, however a right sided fallopian tube cyst was present which had undergone torsion, right sided salpingectomy was performed and the patient was sent home in stable condition on the fourth postoperative day. Keywords: complication, tubal sterilization, tube cyst